Does monetary policy stabilize the exchange rate following a currency crisis? - Ilan Goldfajn; Poonam Gupta (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 1999)
This paper provides evidence on the relationship between monetary policy and the exchange rate in the aftermath of currency crises. It analyzes a large data set of currency crises in 80 countries in the period 1980 to 1998. The main question addressed is: can monetary policy significantly alter the probability of reversing the post-crisis undervaluation through nominal appreciation rather than higher inflation? We find that tight monetary policy facilitates the reversal of currency undervaluation through nominal appreciation rather than inflation. When the economy is also facing a banking crisis, depending on the specification, tight monetary policy may not have the same effect.
Keywords: E44; E63; 330